Research in organizational change and development. Vol. 22 - Shani, A. B. Rami; Noumair, Debra Ann (Emerald, 2014)
These manuscripts provide an intriguing collection that capture and provide value to the real work of creating a sustainable field of study and practice organization change and development and sustainable organizations.
Keywords: Organizational change.; elektronické knihy; electronic books